DECODING THE STRATEGIC ROLE OF INTERNAL CONTROL QUALITY IN MARKET VALUATION: EVIDENCE FROM REAL ESTATE FIRMS LISTED ON THE STOCK EXCHANGE OF THAILAND - Jindaluang, Parisa; Yodbutr, Arunee; Satjasomboon, Sutawan; Yuanyuan, Wang (RMUTT Global Business and Economics Review, 2026)
This research aims to explore the impact of internal control quality on the market value of real estate companies listed on the Stock Exchange of Thailand using secondary data of 110 companies over a 3-year period from 2021 to 2023. The price-to-sales ratio (P/S) is set as the dependent variable, while internal control quality (CG) is converted into a categorical variable based on the corporate governance score. In addition, the variables of operating profit to revenue (OPM), business size (Log Total Assets), business age, and financial risk (Debt-to-Equity) are controlled. The data are analyzed by using multiple regression.The model test results indicate that the model is appropriate, as shown by a statistically significant F-statistic. Internal control quality exhibits a significantly negative relationship, suggesting that companies with higher governance scores may be undervalued within the Thai real estate industry. Operating profit has a positive influence on the price-to-sales ratio, while both firm size and financial risk also show significant effects positive for firm size and negative for financial risk. The effect of firm age is not statistically significant. An examination of multicollinearity reveals acceptable variance inflation factor values, and the Durbin-Watson statistic confirms the absence of autocorrelation issues. The findings suggest that operating efficiency, capital structure, and firm size remain key drivers of market valuation, whereas internal control quality may exert a short-term negative impact under Thailand’s regulatory conditions. These results have implications for executives in shaping governance policies that balance strict oversight with operational flexibility. From a theoretical perspective, the study contributes to the understanding of internal control’s role inthe real estate sector of developing economies and recommends future research to incorporate ESG disclosure variables and long-term dynamic analysis to validate the observed relationships.